PERBEDAAN TINGKAT ASUPAN ISOFLAVON PADA PASIEN KANKER PAYUDARA DENGAN ORANG SEHAT DI RUMAH SAKIT - , I WAYAN DWIJA KARYASA, dr. Johan Kurnianda, SpPD-KHOM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Breast cancer is non communicable chronic disease the prevalence of which is increasing all over the world, including in Indonesia and particularly East Java. Causes of breast cancer are unknown. Some studies show risk factors of breast cancer are hormonal, genetic, reproductive and endocrinologic factors. There is isoflavon compound in soybeans that is known as anti cancer with anti estrogen activities. Objective: In general the study was aimed to identify the difference in isoflavon intake in breast cancer patients and healthy people in hospitals. Method: The study was analytic observational using matched case control study design at comparison 1:2 with matching on status of menopause. Cases were positive receptor estrogen breast cancer patients newly diagnosed during the first visit at hospital outpatient Oncologic Surgery Polyclinic. Controls were staff considered healthy based on the result of health examination at Dr. Ramelan Naval Hospital of Surabaya. Cases comprised 49 people and controls 98 people taken through consecutive method. Data consisted of identity of samples, weight, height, isoflavon intake, family history, use of hormon replacement therapy and parity. Intake of isoflavon was obtained from Semiquantitative Food Frequency Questionnaire (SQ FFQ) and statistical test used chi square and Odd Ratio (OR). Result: There was difference in isoflavon intake and family history between cases and controls (p<0.05) and there was association between isoflavon intake and (OR:2.85